2016
DOI: 10.1177/1541931213601244
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and Application of 3D Ear Images For Earphone Design

Abstract: Detail anthropometric dimensions and a 3D shape of the outer-ear are applicable to design ear-related products such as an earphone. However, 3D scanning of the ear part is quite difficult due to a complex shape of the ear, also detailed ear dimensions which are needed to be measured for earphone design were not identified in previous studies. This study collected 3D scan images of the whole outer-ear from 100 Korean participants (50 females and 50 males) aged 20 to 59, then measured their detailed ear dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 20 publications
(30 reference statements)
0
18
0
Order By: Relevance
“…Moreover, Lee et al (2016) revealed that ear dimensions selected in previous studies could not provide sufficient data for earphone design. For example, curvatures of the ear root were considered as an important factor for holding ear‐band products, such as ear‐band earphones, headphones, and glasses design (Lee et al, 2016). These studies highlighted the importance of different ear dimensions when designing different products, and addressed the requirements of the market to explore more ear anthropometric information for the design.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, Lee et al (2016) revealed that ear dimensions selected in previous studies could not provide sufficient data for earphone design. For example, curvatures of the ear root were considered as an important factor for holding ear‐band products, such as ear‐band earphones, headphones, and glasses design (Lee et al, 2016). These studies highlighted the importance of different ear dimensions when designing different products, and addressed the requirements of the market to explore more ear anthropometric information for the design.…”
Section: Discussionmentioning
confidence: 99%
“…After anthropometric information was chosen, physical fit and comfort perception were studied to link anthropometric data with industrial design. Lee et al (2016) examined the physical fit between product and ear anthropometry. In the study, a virtual fit analysis was conducted when the designed ear‐tip earphones were placed on 3D ear models.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations